Android programming : the Big Nerd Ranch guide - Phillips, Bill (Big Nerd Ranch, 2013)
Android Programming: The Big Nerd Ranch Guide: is an introductory Android book for programmers with Java experience. Based on Big Nerd Ranch's popular Android Bootcamp course, this guide will lead you through the wilderness using hands-on example apps combined with clear explanations of key concepts and APIs. This book focuses on practical techniques for developing apps compatible with all versions of Android widely used today (Android 2.2 - 4.2). Write and run code every step of the way – creating apps that catalog crime scenes, browse photos, track your jogging route, and more. Each chapter and app has been designed and tested to provide the knowledge and experience you need to get started in Android development. Write and run code every step of the way — creating apps that catalog crime scenes, browse photos, track your jogging route, and more. Each chapter and app has been designed and tested to provide the knowledge and experience you need to get started in Android development. " Big Nerd Ranch provided the training we needed to get hundreds of engineers building skillfully on Android. This book is a great distillation of that training and will be a huge help to anyone looking to ramp up as well. " – Mike Shaver, Director of Mobile Engineering, Facebook " …a must-have for the developer just starting in Android or ready for more advanced techniques. I was impressed with this book's content and clarity of presentation. The authors explain simple and complex Android topics with equal ease. " – James Steele, author of The Android Developer's Cookbook.